PENDAMPINGAN KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI PEMIMPIN PEMBELAJARAN PADA PROGRAM SEKOLAH PENGGERAK KOTA BONTANG - Mohammad Salehudin; Suparmi Suparmi; Nurdaniati Nurdaniati; Panggih Panggih; Hani Subakti (As-Sidanah, 2024)
The principal has many roles and duties, apart from being an administrative leader, motivator, leader and so on. However, not all school principals have the ability to provide learning leadership because, in the independent curriculum, the duties and roles of school principals become strategic as learning leaders. The service aims to find out the participants' views independently about instructional leadership abilities and the competence of school principals in implementing driving schools. This activity uses strategies carried out to achieve the expected conditions using the Participatory Action Research (PAR) method, namely mentoring with involvement and involving other parties to make changes while the parties are involved. The form of participation in this leadership workshop is Teachers' Halls East Kalimantan Mobilizer, Mobilization School Facilitator and principal of the mobilization school in Bontang City. The result of service and mentoring is that the school principal has well-defined competencies and can carry out driving school leadership to implement the independent curriculum very well and precisely. Reflections on the results of mentoring need to be developed in the implementation of the Merdeka curriculum with the competence of school principals, which includes: (1) Principals support their schools in becoming a comfortable and safe environment to become a good, harmonious ecosystem and in accordance with the expectations of students learning at school; (2) Establish relationships between school residents. to carry out communication and interaction that contains mutual trust and mutual care; (3) In the school environment as a learning environment as an ecosystem which is structured as a policy to receive student input and aspirations; and (4) Involve students tinbbuildinga conducive learning environment for all students. The implications of mentoring for improving the performance of school principals and developing the concept of a better learning ecosystem.